1996
DOI: 10.1063/1.471784
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating conformation dependence and nonadiabatic effects in the photodissociation of allyl chloride at 193 nm

Abstract: The experiments presented here investigate the competing photodissociation pathways for allyl chloride upon excitation of the nominally ππ*(C=C) transition at 193 nm. The measured photofragment velocity distributions evidence C–Cl bond fission and HCl elimination. The recoil kinetic energy distribution for the HCl products is bimodal, indicating two primary processes for HCl elimination. The experimental measurements show C–Cl bond fission dominates, giving an absolute branching ratio of HCl:C–Cl=0.12±0.03 whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
(10 reference statements)
1
17
0
Order By: Relevance
“…These results suggest that allyl chloride should show increased branching to the C-Cl bond fission channel relative to vinyl chloride. The recent experimental results of Myers and co-workers 6 show a branching ratio of C-Cl fission to HCl elimination of 1:0.11 which is indeed larger than the ratio of 1:1 that had been previously measured for vinyl chloride by Umemoto and co-workers 1 .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…These results suggest that allyl chloride should show increased branching to the C-Cl bond fission channel relative to vinyl chloride. The recent experimental results of Myers and co-workers 6 show a branching ratio of C-Cl fission to HCl elimination of 1:0.11 which is indeed larger than the ratio of 1:1 that had been previously measured for vinyl chloride by Umemoto and co-workers 1 .…”
Section: Discussionmentioning
confidence: 57%
“…Experimental work in our laboratory indicates that in cases of weak coupling of the relevant configurations, bond fission is further suppressed by nonadiabatic transitions at the barrier and subsequent recrossing and return to the Franck Condon region. 25 With these ideas in mind, and in light of recent crossed lasermolecular beam experiments of Myers and co-workers 6 which compare the branching between C-Cl bond fission and HCl elimination channels between vinyl and allyl chloride, we can determine if the trends of the relative contribution of nσ* character in the Franck-Condon region follow the trends of the experimental results. Our emission spectra and our calculations show that the initial excitation in gauche-allyl chloride (the dominant conformer) has some nσ* character.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the lowkinetic-energy and high-kinetic-energy C-Br fission processes contributing to the m/e ) 79 spectrum have differing anisotropies, it would be necessary to correct each of their relative contributions to the P(E T ) by a factor of (1 + /4) -1 . In studies of the photodissociation of analogous halogenated unsaturated hydrocarbons resulting from excitation in the ππ * absorption band, the anisotropy of the carbon-halogen fission has typically been found to be small, 14 due in part to the existence of multiple Figure 2. The slightly underfit signal at arrival times greater than 200 µs is too slow to be due to photodissociation of 2-bromo-1-butene or its dimer, and may be the result of beam scatter.…”
Section: Results and Analysismentioning
confidence: 99%
“…It was shown that a sufficient condition for a nonvanishing channel phase is that the state reached by two coherent paths be coupled to a continuum, either as a discrete state embedded in a continuum or as a continuum state inelastically coupled to a second continuum. 6 This condition is satisfied here inasmuch as the initially excited 1 AЈ͑ , * ͒ state is coupled to the 1 AЉ͑ , * ͒ state in a twisted configuration 25,26 and to the continuum region of the ground state ͑see Fig. 12͒.…”
Section: B Coherent Control Of Vinyl Chloridementioning
confidence: 95%